Adaptive simulation and integration method for wheel-rail contact problems in locomotive traction studies. Issue 12 (2nd December 2022) - Spiryagin, Maksym; Shrestha, Sundar; Persson, Ingemar; Wu, Qing; Arango, Esteban Bernal; Cole, Colin
Abstract : Knowledge of creep forces at wheel-rail interface when high power is applied to the locomotive wheels has been the subject of many recent studies. The common wheel-rail interaction methods are generally divided by two theories – Hertzian and non-Hertzian. The first method uses Hertzian contact for the normal problem and the tangential problem is divided into two algorithms – Polach's theory and the Simplified theory-based algorithm referred to as Modified Fastsim. Kalker's original Fastsim-based method shows a better accuracy for these two Hertzian-based algorithms. The second method is based on the non-Hertzian theory, and it uses the Exact theory also developed by Kalker and implemented in the Extended Contact library to calculate forces at the wheel-rail interface. Considering that the second method is more accurate, this paper aims to present an adaptive simulation and integration method (ASIM) which is positioned in the middle between the two common methods and is designed to introduce a transition from the non-Hertzian to Hertzian contact in the normal problem with the application of the Modified Fastsim for the calculation of contact forces at the wheel-rail interface. The proposed method is aimed to be used in vehicle system dynamics studies performed in multibody software packages. A specially developed wheel-rail coupling incorporating geometrical, normal, and tangential modules is integrated into Gensys multibody software and benchmarked with the standard Extended Contact based wheel-rail coupling by means of locomotive traction tests that use a full mechatronic model of a high adhesion locomotive. The computational performance and accuracy of the proposed method are assessed and discussed.